Simulasi Besaran Pinjaman terhadap Permohonan Kredit Menggunakan Monte Carlo - Satra Murka (Jurnal Informatika Ekonomi Bisnis, 2021)
Providing credit to customers is a very important part for PT. BPR LPN Tarantang in increasing a profit. Credit is the provision of the use of money or goods to other people within a specified period of time with guarantee or without collateral, by providing interest or non-interest services. In banking management it is very necessary to determine the amount of the credit loan, so that the amount of the loan customer credit can be. fulfilled. This study conducted credit loan data from 2017 to 2019. To speed up data processing on the amount of credit loans, a Web-based program with the PHP programming language was applied. The result of the test is to get a prediction of the loan size with an accuracy rate of 92%. So that the results obtained can help the company PT. BPR LPN Tarantang in predicting the amount of credit in the coming year.